ANALISIS PARTISIPASI BELAJAR SISWA KELAS V SDN 71 MACCINI KECAMATAN LILIRIAJA KABUPATEN SOPPENG DALAM PEMBELAJARAN IPAS - Sudarto, Sudarto; Mujahidah, Mujahidah; Putri Nurhalizah, (Jurnal Cakrawala Ilmiah, 2025)
This study is a descriptive qualitative study that aims to describe the student learning participation in IPAS learning. The subjects in this study were of the teachers and the students of the fifth grade at SDN 71 Maccini. The research data collection techniques used were interview, observation and questionnaire techniques. The data analysis techniques of this study were data reduction, data presentation and drawing conclusions. Results and conclusions: The learning participation of students of grade V of SDN 71 Maccini, Liliriaja District, Soppeng Regency in science learning are (1) Students are enthusiastic, enthusiastic, active in asking and answering questions, active in discussions and group work, have the initiative in seeking information through various sources, and have the courage and confidence in conveying the results of group discussions in front of the class.